High Power 980-nm Broad-Area Lasers with Distributed Bragg Reflection Grating. Issue 1 (2nd September 2021) - Qiao, Chuang; Fang, Dan; , Li; Fang, Xuan; Tang, Jilong; Wang, Dengkui; Zhang, Baoshun; Wei, Zhipeng
Abstract: High-power and highly stable 980 nm semiconductor lasers are widely used in fiber laser pumping and instrumentation applications. We report on a distributed Bragg reflector (DBR) semiconductor laser manufactured on the waveguide structure of an asymmetric large optical cavity. Wavelength stabilization is achieved using a 500-µm-long DBR with a sixth-order Bragg grating, which is fabricated using a combination of electron beam lithography and inductively coupled plasma etching. When the device injection current is 22 A, the output power ranges up to 16 W, the slope efficiency is 0.73 W/A, and a spectral linewidth of 1.4 nm is achieved.